Genomic Editing: The Evolution in Regulatory Management Accompanying Scientific Progress - Goberna, María Florencia; Whelan, Agustina Inés; Godoy, Perla; Lewi, Dalia Marcela (Frontiers in Bioengineering and Biotechnology, 2022)
Argentina currently has a regulation for genome-editing products whose criteria were updated as consultations were received to determine the regulatory status of these products. The aim of this regulation is to consider all organisms (animals, micro-organisms and plants) under the same NBT resolution independently and without being linked to commercial Genetically Modified Organism (GMO) regulations. This gives certainty to local researchers and developers (teams of local developers and researchers), which can be seen in the number of developments and consultations carried out. It should be noted that early results showed that the speed of innovation of these technologies was increasing in a short time, giving more opportunity to local developers who showed interest in generating products in different species, crops and phenotypes.